Correlation of Functional Outcomes and Sagittal Alignment After Long Instrumented Fusion for Degenerative Thoracolumbar Spinal Disease. Issue 19 (1st October 2018) - Yeh, Kuang-Ting; Lee, Ru-Ping; Chen, Ing-Ho; Yu, Tzai-Chiu; Liu, Kuan-Lin; Peng, Cheng-Huan; Wang, Jen-Hung; Wu, Wen-Tien
Abstract : Study Design: A retrospective function and radiography study of the patients who have received long instrumented thoracolumbar fusion. Objective: To investigate the correlation between the sagittal spinopelvic alignment and the functional outcomes after long instrumented fusion for degenerative thoracolumbar spinal disease. Summary of Background Data: Restoring better sagittal alignment is known as a key factor to spine fusion surgeries. The relationship between function and radiographic results in the elderly group is barely known. Methods: Between 2009 and 2013, data of 120 patients with multilevel degenerative thoracolumbar spinal disease who underwent long instrumented fusion were collected retrospectively. Perioperative radiographic and functional parameters were measured and analyzed for their correlations. Receiver operating characteristic (ROC) method was used to define ideal cutoff points of postoperative spinopelvic alignment to avoid poor outcome. Results: Oswestry disability index (ODI) more than or equal to 20 or Visual analogue scale (VAS) more than or equal to 4 were defined as poor functional outcomes. The optimal cutoff points of the radiographic parameters were found as below: the mismatch between pelvic incidence and lumbar lordosis was 16.2°, sagittal vertical axis was 38.5 mm, and pelvic tilt was 23.4°. Poor functional outcomes were significantly correlated with bad sagittal alignment, older age, and poor preoperative function. Conclusion: Postoperative functional outcomes were highly impacted by the spinopelvic sagittal alignment. Level of Evidence: 4